TOPENG RANGDA AS METAPHOR OF DEWI DURGA BY TJOKORDA OKA TUBLEN - Artawan, Cokorda Alit; Mudra, I Wayan; Muka, I Ketut; Karja, I Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
The Topeng Rangda created by Tjokorda Oka Tublen with a distinctive character as an interpretation of Durga has a magical impression. This research aims to deeply understand Rangda as a metaphor of Durga by Tjokorda Oka Tublen. The Topeng Rangda created by Tjokorda Oka Tublen's is sacred to the community and used as a role model by the Balinese people. Nevertheless, until now there has been no special study about it. This research uses a qualitative method. The data collection is done by purpose sampling with observation, interview, and literature study techniques, dissected with aesthetic theory and metaphor theory. The result of this study, Topeng Rangda as a metaphor is a mask with a scary face as the embodiment of Dewi Durga in white with buck teeth, bulging eyes with a magical, majestic and authoritative impression. The process of creating Tjokorda Oka Tublen's mask includes: newasen, nyawi, nyalonan, makalan, nadiang, nelesang, ngalusang, ngewarna, dan pasupati.